Determination of Attitudes of University Students towards Domestic Violence. - Dissiz, Melike; Yalcinturk, Aydan Akkurt (International Journal of Caring Sciences)
Background: Domestic violence against women both in the world and in our country is an important community and women's health problem. Objective: The aim of this study was to determine the attitudes of students studying in Health Sciences to domestic violence. Methodology: A total of 450 students attending the first, second and third grade of the Faculty of Health Sciences and Nursing Faculty in the 2018-2019 school year participated in this study, which is descriptive and cross-sectional type. Sample selection was not made, and the entire universe was tried to be reached. Data were collected between 15 October 2018 and February 2019 using "Information Form" and "Attitude Scale towards Domestic Violence". Data were collected by using the "Scale of Attitudes Towards Violence Against Women" by questionnaire method. Data evaluated with SPSS (Statistical Package for the Social Sciences) program. Results: The mean age of the students was 19.70 ± 1.60 and most of them were girls (87.6%) and half of them (50.2%) were in the faculty of health sciences. The study found that 18.9% of the students witnessed violence, 16.7% were subjected to violence by their parents and the most verbal violence in the family (12.7%). According to the domestic violence scale, it was determined that male students' tendency to hide violence and negative attitudes related to violence were significantly higher than female students (p <0.05). Significant differences were found between the regions where the students lived according to the sub-dimension of the reasoning the violence scale of domestic violence (p <0.05). Conclusion: In the study, it was determined that male students conceal violence in the family more, had a negative attitude towards violence against women and students coming from Eastern Anatolia Region more reasoning the violence for university education.